Pompastiškoji (NE)kasdienybė Bohemijos Karalystėje - Račickas, Ignas (Lietuvos istorijos studijos, 2025)
Rec.:František Šmahel, Martin Nodl, Václav Žůrek (eds.), Festivities, Ceremonies and Rituals in the Lands of the Bohemian Crown in the Late Middle Ages, Leiden, Boston: Brill, 2022.